Bored Together: The Friendship of “Filling Time” in Child and Youth Mental Health Nursing - Davey Hamada (Journal of Applied Hermeneutics, 2025)
In this article, I argue that, on locked child and youth mental health units, friendships can form between patients and nurses. This may occur due to the confined nature of such settings, which gives rise to feelings of boredom. Boredom can be thought of as a stimulus or meaning deficit. Phenomenologically, it may be experienced as a dragging of time, restlessness, and a desire to do something else. Nurses often feel responsible for relieving the boredom of patients by engaging them in conversation or recreational activities. However, this ignores the fact that nurses experience boredom as well. One understanding of friendship, in this context, could be that friendship starts with a mutual understanding of the boredom of the other. Friendship is conventionally frowned upon by nursing regulators. However, in this paper, I argue that their views are based on a particular kind of friendship derived from the Western tradition—that which has normative characteristics and is incompatible with hierarchy. Using both aspects of Western and Confucian thought, I challenge this perspective, arguing that aspects of friendship do indeed show up in nurse-patient relationships and that they are not necessarily problematic. Using examples from my own practice, I aim to show that nurses and patients may involve each other symbiotically in shared meaning-making, especially in confined spaces such as the mental health ward. Nurses and patients mutually participate in a filling of “empty time,” demonstrating that even in confinement, there is the possibility of friendship.